Fuel cycle scheme design and evaluation for thorium–uranium breeding recycle in CANDU reactors. (May 2016) - Yang, Bo; Shi, Jianfeng; Bi, Guangwen; Tang, Chuntao
Highlights: This work is to develop a fuel cycle scheme for thorium–uranium breeding recycle in CANDU reactors. The roadmap of thorium–uranium breeding recycle is promoted based on the neutronics theory and numerical analysis. We report the fuel management strategy, spent-fuel characteristics and resource utilization evaluation. Abstract: This work is aimed to develop a fuel cycle scheme for thorium–uranium breeding recycle in CANDU reactors. According to the neutronics theory on the breeding of fissile nuclides in nuclear fuel system, the prerequisite of 232 Th– 233 U breeding is revealed in CANDU fuel system and a roadmap of thorium–uranium breeding recycle in CANDU reactors is promoted. Following the roadmap, the thorium-based fuel cores were designed and the neutronics performance was evaluated. A CANDU-6 core with rated thermal power of 2061 MW was taken as the reference core. Based on the fuel management strategy, the spent-fuel characteristics for employed fuel types were assessed, including radiotoxicity, decay heat and gamma rays. Finally, the thorium–uranium breeding recycle schemes were established and evaluated in contrast with natural uranium once-through cycle, widely applied in operational CANDU reactors. The design and evaluation results indicated that the Th-U breeding recycle is technically feasible in current CANDU reactors.